Phantom radiculopathy: a rare postoperative phenomenon - Archunan, Maheswaran (BMJ Case Rep, 2020)
Limb amputations are carried out for a number of reasons, which include trauma, vascular disorders, infection, oncology and congenital abnormalities. These patients can develop multiple complications postoperatively with phantom limb pain being a well-recognised issue. That being said, phantom radiculopathy is far less encountered and can therefore be easily overlooked. There are limited cases described in literature and as a result pathophysiology is poorly understood. In this report, we present a patient who had developed phantom radiculopathy decades after his left above knee amputation surgery, which was performed after a road traffic accident. However, we were successfully able to treat the patient with foraminal epidural corticosteroid injection.